Intestinal resident macrophages: Multitaskers of the gut. Issue 8 (28th March 2020) - Viola, Maria Francesca; Boeckxstaens, Guy
Abstract: Background: Intestinal resident macrophages play a crucial role in homeostasis and have been implicated in numerous gastrointestinal diseases. While historically believed to be largely of hematopoietic origin, recent advances in fate‐mapping technology have unveiled the existence of long‐lived, self‐maintaining populations located in specific niches throughout the gut wall. Furthermore, the advent of single‐cell technology has enabled an unprecedented characterization of the functional specialization of tissue‐resident macrophages throughout the gastrointestinal tract. Purpose: The purpose of this review was to provide a panorama on intestinal resident macrophages, with particular focus to the recent advances in the field. Here, we discuss the functions and phenotype of intestinal resident macrophages and, where possible, the functional specialization of these cells in response to the niche they occupy. Furthermore, we will discuss their role in gastrointestinal diseases.